Pengaruh Pembiasaan Tadarus Al-Qur’an Terhadap Terbentuknya Karakter Religius Siswa Kelas XI Di SMAN 1 Kota Bogor - Santi Lisnawati; Riva Farisha (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The world of education has many goals to be achieved, one of which is to foster religious character and develop good character in students. By habituating the recitation of the Qur'an in schools, students should be able to understand and form a religious character in themselves. This study aims to determine the level of habituation of the recitation of the Qur'an of class XI students at SMAN 1 Bogor City, to determine the level of religious character of class XI students at SMAN 1 Bogor City and to determine whether there is an influence of the habituation of the recitation of the Qur'an on the religious character of class XI students at SMAN 1 Bogor City. The research method used in this study is quantitative research. This study used a population of all eleventh-grade students at SMAN 1 Bogor City, with a sample of 159 students drawn randomly. The instruments used in this study were questionnaires and documentation. The data analysis technique used simple linear regression analysis with the help of SPSS 20 application.The results of the study show that: First, the habit of Al-Qur'an recitation of grade XI students at SMAN 1 Bogor City obtained a value in the "very good" category with an average value (mean) of 48.54. Second, the religious character of grade XI students at SMAN 1 Bogor City obtained a value in the "good" category with an average value (mean) of 46.02. And third, the results of the simple linear regression test obtained a calculated t value of 27.741> t table 1.654, a sig value of 0.000 <0.05 and a coefficient of determination value of 0.831 so that Ho is rejected and Ha is accepted which means there is a significant influence between the habit of Al-Qur'an recitation on the religious character of grade XI students at SMAN 1 Bogor City by 83.1% while the remaining 16.9% is influenced by other factors.